Answer:
Given,
f(x)=x^2+6
g(x)=2x-1
Now,
g[f(x)]=g(x^2+6) since f(x)=x^2+6
=2(x^2+6)-1 since x > x^2+6
=2x^2+12-1
=2x^2+11
Answer:
6/x^2
Step-by-step explanation:
Simplify the following:
2/x^2 + 4/x^2
2/x^2 + 4/x^2 = (2 + 4)/x^2:
(2 + 4)/x^2
2 + 4 = 6:
Answer: 6/x^2
Answer: 16t^6−40t^3+25 is the answer
first lets set the equation as a binomial *remember 2 binomial= trinomial*
so its going to look something like..........
(4t^3-5) (4t^3-5)
now we do the foil method so 4t^3* 4t^3= 16t^6 (add exponents)
do the same for the other terms:
4t^3*-5= -20t^3
-5*4t^3= -20t^3
-5*-5= 25
now the whole equation is...
16t^6-20t^3-20t^3+25 (combine like terms like -20t^3 and -20t^3)
therefor the answer is... 16t^6-40t^3+25
The graph on the left is correct
Answer:
The equivalent expression is - 25n - 2 and it matches with option D.
Step-by-step explanation:
We have to simplify and create the equivalent expression for
{- 2(- 5n + 6) + 5(2 - 7n)}
Now, {- 2(- 5n + 6) + 5(2 - 7n)}
= 10n - 12 + 10 - 35n
= - 25n - 2
Therefore, the equivalent expression is - 25n - 2 and it matches with option D. (Answer)